Mobile learning medium for junior high math interest: how is it developing? Is it effective? - Lubis, Maesaroh; Naim, Muhammad Ainun; Riono, Sapto Hadi; Silva, Samuel Da (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
In today's digital era, education requires innovation to enhance students' interest in learning, especially in mathematics, which is often perceived as challenging. This study targets the development of mobile learning-based media for MTs students in Pasuruan Regency, aiming to boost student engagement and participation in mathematics. Nine grade IX students participated as subjects in this study. Employing the 4D development model (Define, Design, Develop, Disseminate), the research sought to create learning media that is valid, practical, and effective. Instruments included questionnaires to evaluate student effectiveness and interest, alongside expert validation for content and media. The findings revealed that the mobile learning media achieved rigorous standards, with positive feedback from both experts and students. Notably, 78% of students reported that the media facilitated a better understanding of mathematics topics such as algebra and geometry, which were previously difficult. Additionally, 85% of students exhibited increased interest in learning following the use of this media. The data further indicated a 25% improvement in mathematics comprehension post-implementation. These results suggest that the mobile learning media is effective in enhancing both interest and understanding of mathematics, making it a viable tool for educational settings. This study makes a valuable contribution to enriching learning methodologies that are accessible anytime, anywhere, offering students greater learning flexibility.